FINTECH ADOPTION AND ENTREPRENEURIAL EXPERIENCE: KEY DRIVERS OF MSME SUSTAINABILITY: English - Lasmi, Ni Wayan; Putra, Komang Widhya Sedana; Laksmi, Kadek Wulandari (DAS Institute, 2024)
The rapid development of digital technology has significantly impacted various sectors, especially entrepreneurship, with financial technology (fintech) emerging as one of the key innovations. Fintech offers easier access to financial services, which can improve financial management for small and medium-sized enterprises (SMEs). However, the effectiveness of fintech adoption may depend on the entrepreneurial experience of business owners, especially among young entrepreneurs, as it influences their ability to leverage fintech tools for better financial management and sustainability. This study aims to explore how fintech usage affects the sustainability of MSMEs in Bali and examines the moderating role of entrepreneurial experience in this relationship. A purposive sampling method was used to survey 200 MSMEs in Bali, collecting data through questionnaires. The collected data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess the relationships between fintech usage, entrepreneurial experience, and MSME sustainability. The results indicate that both fintech usage and entrepreneurial experience have a positive impact on MSME sustainability. Additionally, entrepreneurial experience was found to moderate the relationship between fintech adoption and MSME sustainability, suggesting that experienced entrepreneurs are better equipped to harness the potential of fintech for financial management. This study highlights the importance of combining digital tools with entrepreneurial expertise to improve the sustainability and competitiveness of MSMEs in the digital economy.